Influence of CYP2D6 and CYP3A5 Polymorphisms on the Pharmacokinetics and Pharmacodynamics of Bisoprolol in Hypertensive Chinese Patients - Chan, Sze Wa; Chu, Tanya T. W.; Ho, Chung Shun; Kong, Alice P. S.; Tomlinson, Brian; Zeng, Weiwei (Frontiers in Medicine, 2021)
Purpose: This study was performed to investigate the effects of common polymorphisms in CYP2D6 and CYP3A5 on the plasma concentrations and antihypertensive effects of bisoprolol in hypertensive Chinese patients. Methods: One hundred patients with essential hypertension were treated with open-label bisoprolol 2.5 mg daily for 6 weeks. Clinic blood pressure (BP) and ambulatory BP (ABP) were measured after the placebo run-in and after 6 weeks treatment. Peak plasma concentrations of bisoprolol were measured at 3 hrs after the first dose and 3 hrs after the dose after 6 weeks treatment. Trough levels were measured before the dose after 6 weeks treatment. Bisoprolol plasma concentrations were measured with a validated liquid chromatography tandem mass spectrometry method. Six common polymorphisms in CYP2D6 and the CYP3A5*3 polymorphism were genotyped by TaqMan® assay. Results: After 6 weeks of treatment, clinic BP and heart rate were significantly reduced by 14.3±10.9/8.4±6.2 mmHg (P < 0.01) and 6.3±7.6 BPM (P < 0.01), respectively. Similar reductions were seen in ABP values. Bisoprolol plasma concentration at 3 hrs after the first dose and 3 hrs post-dose after 6 weeks of treatment were significantly associated with baseline body weight (P < 0.001) but there was no significant effect of the CYP2D6 and CYP3A5 polymorphisms on these or the trough plasma concentrations. There was no significant association of the CYP2D6 and CYP3A5 polymorphisms or plasma bisoprolol concentrations with the clinic BP or ABP responses to bisoprolol. Conclusion: Bisoprolol 2.5 mg daily effectively reduced BP and HR. The common polymorphisms in CYP2D6 that were examined and the CYP3A5*3 polymorphism appear to have no benefit in predicting the hemodynamic response to bisoprolol in these patients.